PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY TERHADAP HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS VIII MTsN 1 KOTA PADANG - Zahra, Refina; Nasution, Minora Longgom (Departemen Matematika, 2024)
For students, achieving positive learning outcomes is extremely important. In reality, the mathematics learning accomplishment of class VIII understudies at MTsN 1 Kota Padang is still somewhat low. So, the solution given is Two Stay, Two Stray (TSTS). This research is included in the quasi-experiment category with a nonequivalent post-test-only control group design. Class VIII MTsN 1 Kota Padang students are the population. By analysing the final test using Mini Tab software, the study's findings had a significance level of = 0.05 and a P-value of 0.000. This indicates that the achievement of math learning results for class VIII understudies at MTsN 1 Kota Padang who follow the TSTS cooperative learning models is superior to that of students who adhere to standard education.Keywords– Learning outcomes, Two Stay Two Stray